62.4k views
5 votes
Please help on this math question

Please help on this math question-example-1
User Fidd
by
4.9k points

1 Answer

6 votes

Answer:


\large\boxed{C.\ (-2x^2-x+72)/(8x^2)}

Explanation:


(9)/(x^2)-(2x+1)/(8x)=(9\cdot8)/(x^2\cdot8)-((2x+1)\cdot x)/(8x\cdot x)\qquad\text{use the distributive property}\\\\=(72)/(8x^2)-(2x^2+x)/(8x^2)=(72-(2x^2+x))/(8x^2)=(72-2x^2-x)/(8x^2)\\\\=(-2x^2-x+72)/(8x^2)

User Marknorkin
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.